Regulatory T Cells Accumulate in the Lung Allergic Inflammation and Efficiently Suppress T-Cell Proliferation but Not Th2 Cytokine Production - Lucas Faustino; Daniel Mucida; Alexandre Castro Keller; Jocelyne Demengeot; Karina Bortoluci; Luiz Roberto Sardinha; Maisa Carla Takenaka; Alexandre Salgado Basso; Ana Maria Caetano Faria; Momtchilo Russo (Clinical and Developmental Immunology)
Foxp3+CD25+CD4+ regulatory T cells are vital for peripheral tolerance and control of tissue inflammation. In this study, we characterized the phenotype and monitored the migration and activity of regulatory T cells present in the airways of allergic or tolerant mice after allergen challenge. To induce lung allergic inflammation, mice were sensitized twice with ovalbumin/aluminum hydroxide gel and challenged twice with intranasal ovalbumin. Tolerance was induced by oral administration of ovalbumin for 5 consecutive days prior to OVA sensitization and challenge. We detected regulatory T cells (Foxp3+CD25+CD4+ T cells) in the airways of allergic and tolerant mice; however, the number of regulatory T cells was more than 40-fold higher in allergic mice than in tolerant mice. Lung regulatory T cells expressed an effector/memory phenotype (CCR4highCD62LlowCD44highCD54highCD69+) that distinguished them from naive regulatory T cells (CCR4intCD62LhighCD44intCD54intCD69−). These regulatory T cells efficiently suppressed pulmonary T-cell proliferation but not Th2 cytokine production.